The Palaokarst of Chios and Pholegandros - types of widespread karst generations in Greece - RIEDL, H. (Bulletin of the Geological Society of Greece, 2001)
In contrast to the Miocene polje karst (Chios) with deeply incised v-shaped valleys and kehltôler the Plio/Pleistocene polje karst (Pholegandros) is marked by the association of pediments, glacis and coastal marginal pediments. Moreover the axes of the karst basins don’t reach some decakilometers like in the case of the Miocene poljes, but only a few kilometers of length. Typical of the Plio/Pleistocene karst is the absence of open ponors and often dominates the diffuse drying up of the winterly precipitation on allochthonous sandy clay-fillings of the polje’s bottom. The genesis of both palaeokarst types is closely controlled by the palaeoclimate